FORMULASI DAN PENENTUAN NILAI SUN PROTECTION FACTOR (SPF) SEDIAAN KRIM TABIR SURYA EKSTRAK ETANOL BEKATUL PADI BERAS MERAH (Oryza sativa L) - Novita Dewi; Rahayu Utami; Mustika Furi; Melzi Octaviani; Wira Noviana Suhery (Jurnal Penelitian Farmasi Indonesia, 2021)
Study of formulation of sunscreen cream with ethanolic extract of red rice bran (Oryza sativa L) and determining the SPF value in vitro using a UV spectrophotometer has been carried out. Ethanol extract of red rice bran has been shown antioxidant activity. Determining the SPF value due to determine the ability of the red rice bran ethanol extract to protect the skin from UV radiation. Ethanol extract of red rice bran was formulated in the form of a cream type o/w of F1 and F2 containing extract concentrations of 5% and 10%, respectively. Based on the research conducted, it was found that F2 had a higher SPF value of 13,098 than F1 of 11,861. Based on the SPF value generated from the formula, this study showed that the sunscreen cream preparation of red rice bran extract can protect the skin from UV radiation maximally for 110-130 minutes.